Studying global Pentecostalism : theories and methods - Anderson, Allan (Anthropology of Christianity ;, 2010)
With its remarkable ability to adapt to many different cultures, Pentecostalism has become the world's fastest growing religious movement. More than five hundred million adherents worldwide have reshaped Christianity itself. Yet some fundamental questions in the study of global Pentecostalism, and even in what we call "Pentecostalism," remain largely unaddressed. Bringing together leading scholars in the social sciences, history, and theology, this unique volume explores these questions for this rapidly growing, multidisciplinary field of study. A valuable resource for anyone studying new form.